6-1: Operations on Functions (Composition of Functions) I can find the composition of functions
Composition of functions Putting one function into another function
Composition of functions Putting one function into another function Two ways of writing: f₀g(x) = f(g(x))
Composition of functions Putting one function into another function Two ways of writing: f₀g(x) = f(g(x)) Replace the “x” in f(x) with “g(x)”
Ex: f(x) = 2x – 5 g(x) = 4x
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) =
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x))
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x)
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2( ) – 5
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5 g₀f(x)
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5 g₀f(x) = g(f(x)) =
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5 g₀f(x) = g(f(x)) = 4( )
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5 g₀f(x) = g(f(x)) = 4(2x – 5)
Ex: f(x) = 2x – 5 g(x) = 4x f₀g(x) = f(g(x)) = f(4x) = 2(4x) – 5 = 8x – 5 g₀f(x) = g(f(x)) = 4(2x – 5) = 8x – 20
HW: 27-49 all, 52-54 all